Cation Effect on the Binary and Ternary Phase Behaviors of Double‐Tailed Methanesulfonate Amphiphiles. Issue 3 (10th February 2021) - Ontiveros, Jesús F.; Hong, Bing; Aramaki, Kenji; Pierlot, Christel; Aubry, Jean‐Marie; Nardello‐Rataj, Véronique
Abstract: A series of symmetrical dialkyl methanesulfonate amphiphiles [DiC n CHSO 3 ] m M ( n = 6, 7, 8) with different counter cations (M m+ = H +, Li +, Na +, K +, Cu 2+, Zn 2+, Mg 2+, Ca 2+, Sc 3+ ) were synthesized in five steps. Their solubility and critical micelle concentration (CMC) in water were determined highlighting a huge effect of the chain length and the nature of the cation. The hydrophilic–lipophilic balance of the surfactants were assessed with the phase inversion temperature (PIT)‐slope method based on the deviation from the PIT of the reference C10 E4 / n ‐octane/0.01 M NaCl(aq) emulsion through addition of increasing amounts of the dialkyl methanesulfonates. The hydrophilicity of the surfactants was thus ranked in terms of dPIT/dxsulfonate . A "cation" scan with the [DiC 6 CHSO 3 ] m M /benzene/water systems at f w = 0.5 was finally performed confirming the hydrophilicity ranking obtained with the PIT‐slope method. It revealed that the [DiC 6 CHSO 3 ] 2 Mg behaves as a "Balanced Surfactant" able to form spontaneously a three‐phase microemulsion system (Winsor III) just in the presence of water and oil, in the same way as the catalytic surfactant dimethyldioctylammonium molybdate, which has the same PIT‐slope.